Uniform confidence bands for functions estimated nonparametrically with instrumental variables - Joel L. Horowitz; Sokbae Lee (Centre for Microdata Methods and Practice (cemmap), 2009)
This paper is concerned with developing uniform confidence bands for functions estimated nonparametrically with instrumental variables. We show that a sieve nonparametric instrumental variables estimator is pointwise asymptotically normally distributed. The asymptotic normality result holds in both mildly and severely ill-posed cases. We present an interpolation method to obtain a uniform confidence band and show that the bootstrap can be used to obtain the required critical values. Monte Carlo experiments illustrate the finite-sample performance of the uniform confidence band.
Keywords: C13; C14; 330; bootstrap; instrumental variables; sieve estimator; uniform confidence band; Schätztheorie; Bootstrap-Verfahren; Nichtparametrisches Verfahren